2009
DOI: 10.1128/cvi.00396-08
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of the Mycobacterium tuberculosis Δ lysA Δ panCD Vaccine in Domestic Cats Infected with Feline Immunodeficiency Virus

Abstract: Feline immunodeficiency virus (FIV)-positive and FIV-negative cats (n ‫؍‬ 4/group) received 2 ؋ 10 6 CFU Mycobacterium tuberculosis ⌬lysA ⌬panCD intramuscularly. Vaccination elicited antibody responses, albeit at lower levels in FIV-positive cats than in FIV-negative cats. Delayed-type hypersensitivity responses were minimal in both groups. No adverse reactions were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The construction, attenuations and safety profiles of the Mtb H37Rv-derived vaccine strains mc 2 6435 and mc 2 6020 have been described previously (15, 2530). Briefly, in strain mc 2 6020, the panCD and lysA loci were deleted to generate a highly replication-attenuated double-auxotroph strain.…”
Section: Methodsmentioning
confidence: 99%
“…The construction, attenuations and safety profiles of the Mtb H37Rv-derived vaccine strains mc 2 6435 and mc 2 6020 have been described previously (15, 2530). Briefly, in strain mc 2 6020, the panCD and lysA loci were deleted to generate a highly replication-attenuated double-auxotroph strain.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, we discovered that M. tuberculosis mutants defective in making the amino acid lysine (37) or the vitamin pantothenate also were highly attenuated (38). After constructing double auxotroph of mutants of M. tuberculosis , we demonstrated that they are very safe and have the ability to generate protection comparable to BCG (3942). …”
Section: Overview Of Key Mutations That Facilitated Gene Transfer In mentioning
confidence: 99%
“…Diagnosis is based on clinical examination, imaging, biopsy with histopathologic examination, culture of aspirates or tissues, and specific immune-based blood assays ( 4 , 8 , 9 ). Intradermal skin tests are generally unreliable for diagnosing tuberculosis in cats ( 10 ).…”
mentioning
confidence: 99%
“…Before implementation of bovine tuberculosis control programs and wide-scale pasteurization of milk, alimentary tract disease was the most common form of tuberculosis in cats ( 7 ); today, lymphadenopathy and cutaneous forms are more common ( 4 ). Diagnosis is based on clinical examination, imaging, biopsy with histopathologic examination, culture of aspirates or tissues, and specific immune-based blood assays ( 4 , 8 , 9 ). Intradermal skin tests are generally unreliable for diagnosing tuberculosis in cats ( 10 ).…”
mentioning
confidence: 99%